Neinvazivna ventilacija pri bolnikih z amiotrofično lateralno sklerozo - Bregant, Tina (Rehabilitacija (Ljubljana), 2018)
Backgrounds: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by progressive decrease in muscle strength, including respiratory muscle weakness, leading to a reduced alveolar ventilation and an increasing demand on respiratory support. Frequently, in patients with ALS, who have respiratory insufficiency, we introduce non-invasive respiratory support - BiPAP mode, which prolongs survival and improves quality of life. Methods: We describe respiratory problems, and measurements we perform routinely in patients with ALS, ALSFRS-r functional rating scale included. Noninvasive ventilation is presented. Results: In selected patients we show different patterns of respiratory support: intermittent; during the night; and continuous NIV. We show the importance of reading from SD card for a comprehensive intervention. Graphically we present results of ventilators's use. Conclusions: In ALS patients special attention should be paid to respiratory function. Knowing the options which are offered in ventilation machinery used, we can promptly and accurately meet the patients's needs and enhance the home use of NIV, hereby prolonging the survival and improving quality of life in patients with ALS who have adapted to NIV easily.
Keywords: ALS; amiotrofična lateralna skleroza; Amyotrophic Lateral Sclerosis; dihalna podpora; dihalne funkcije; rehabilitacija; rehabilitation; respiratory function; respiratory support; vocational rehabilitation